2015
DOI: 10.1038/npp.2015.333
|View full text |Cite
|
Sign up to set email alerts
|

Replication of Epigenetic Postpartum Depression Biomarkers and Variation with Hormone Levels

Abstract: DNA methylation variation at HP1BP3 and TTC9B is modified by estrogen exposure in the rodent hippocampus and was previously shown to be prospectively predictive of postpartum depression (PPD) when modeled in antenatal blood. The objective of this study was to replicate the predictive efficacy of the previously established model in women with and without a previous psychiatric diagnosis and to understand the effects of changing hormone levels on PPD biomarker loci. Using a statistical model trained on DNA methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 57 publications
(73 reference statements)
3
51
1
Order By: Relevance
“…Another behavioral state with a major impact on maternal care is depression, and post‐partum depressive behavior is associated with reduced maternal care in both humans (Field ) and mice (Maguire & Mody ). Interestingly, and apparently consistent with our own notion in mice, it was recently reported that the hyper‐methylation status of the HP1BP3 gene promoter in blood DNA from pregnant women was an excellent antenatal predictor of PPD (Guintivano et al ; Osborne et al ). One potential cause for post‐partum anxiety is altered cholinergic status (Grisaru et al ); however, we excluded that cause by demonstrating that Hp1bp3 −/− mice sustained unchanged circulation cholinesterase activities as compared to normal controls.…”
Section: Discussionsupporting
confidence: 89%
“…Another behavioral state with a major impact on maternal care is depression, and post‐partum depressive behavior is associated with reduced maternal care in both humans (Field ) and mice (Maguire & Mody ). Interestingly, and apparently consistent with our own notion in mice, it was recently reported that the hyper‐methylation status of the HP1BP3 gene promoter in blood DNA from pregnant women was an excellent antenatal predictor of PPD (Guintivano et al ; Osborne et al ). One potential cause for post‐partum anxiety is altered cholinergic status (Grisaru et al ); however, we excluded that cause by demonstrating that Hp1bp3 −/− mice sustained unchanged circulation cholinesterase activities as compared to normal controls.…”
Section: Discussionsupporting
confidence: 89%
“…With respect to perinatal depression, two regions of alternative DNA methylation in association with postpartum depression have been previously identified in leukocytes, resulting from a screen that was designed to identify DNA methylation effects of estrogen activity 25,26 . Later work from this dataset using a candidate-gene approach also identified alterations in methylation density within the oxytocin receptor gene in association with postpartum depression 27 .…”
Section: Molecular Pathways From Early Life Adversity To Adult Perinamentioning
confidence: 99%
“…A challenge for the identification of peripheral tissue-based epigenetic biomarkers in the context of psychiatry is the generalizability of the identified peripheral epigenetic variation in the brain. We have hypothesized previously that circulating steroid hormones such as cortisol may mark peripheral tissue DNA on the epigenetic level while affecting behavior through central nervous system (CNS) specific actions [1517]. In support of this hypothesis, the initial objective of this study was to evaluate if cortisol-associated DNA methylation levels in peripheral tissues (blood and saliva) are enriched among suicide-associated DNA methylation levels in the brain.…”
Section: Introductionmentioning
confidence: 99%